2006
DOI: 10.1007/s00595-006-3213-x
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Repair of an Abdominal Aortic Aneurysm in a Patient with Horseshoe Kidney: Report of a Case

Abstract: Horseshoe kidney is a rare congenital anomaly that may cause various technical problems during conventional repairs of abdominal aortic aneurysms. We report the case of a 68-year-old woman with a horseshoe kidney, symptomatic abdominal aortic aneurysm and mild renal failure. The patient underwent endovascular repair using a bifurcated endoprosthesis. The postoperative was uneventful. We describe the diagnosis and the endovascular technique and literature review. Descriptors: Aortic aneurysm. Aortic aneurysm, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…24 Minor complications have also been reported, such as left groin wound infection 25 and transitional fever. 26 Limitations include the heterogeneous reporting of data, which leads to incomplete data sets in variables of interest; thus, statistical testing derived may be underpowered. Another limitation is the nature of the case reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Minor complications have also been reported, such as left groin wound infection 25 and transitional fever. 26 Limitations include the heterogeneous reporting of data, which leads to incomplete data sets in variables of interest; thus, statistical testing derived may be underpowered. Another limitation is the nature of the case reports.…”
Section: Discussionmentioning
confidence: 99%
“…24 Minor complications have also been reported, such as left groin wound infection 25 and transitional fever. 26…”
Section: Discussionmentioning
confidence: 99%
“…In considering endovascular repair, detailed preprocedural imaging is essential in the assessment of renal vasculature. 23,24 If available, the use of three-dimensional (3D) reconstructions of CT angiography using a 3D workstation (including functions of volume rendering, multiplanner reconstruction and centerline of flow images) is helpful and may offer more information than conventional angiography. 30,31 Although the sacrifice of lower-pole and accessory renal arteries is inevitable, this does not seem to cause significant endoleaks, jeopardize renal function or cause long-term renal hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Volpe et al 24 treated a 65-year-old man with a 5-cm infrarenal aneurysm with a Powerlink bifurcated endograft (Endologix, Irvine, CA, USA), with exclusion of two accessory renal arteries arising from the non-aneurysmatic proximal aortic neck. Sajid et al 25 reported an 80-year-old patient treated with a Cook Zenith aorto-uni-iliac device (William Cook UK) with femorofemoral bypass graft, with intentional covering of two accessory renal arteries arising from the sac.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, ectopic renal arteries are often found in this condition [10]. Since 1991, EVAR has been used for the treatment of AAA coexistent with HSK in 13 cases, and uni-iliac stent grafting was used in most of them [11][12][13][14][15][16][17][18][19]. This method is easier and quicker because theres is no need to catheterize the contralateral limb.…”
Section: Discussionmentioning
confidence: 99%